Prognostic significance of immune reconstitution following CD19 CAR T‐cell therapy for relapsed/refractory B‐cell lymphoma - Sophia Stock; Veit L. Bücklein; Viktoria Blumenberg; Giulia Magno; Alica‐Joana Emhardt; Alessandra M. E. Holzem; David M. Cordas dos Santos; Christian Schmidt; Stefanie Grießhammer; Lisa Frölich; Sebastian Kobold; Michael vonBergwelt‐Baildon; et al. (HemaSphere)
Abstract Immune deficits after CD19 chimeric antigen receptor (CAR) T‐cell therapy can be long‐lasting, predisposing patients to infections and non‐relapse mortality. In B‐cell non‐Hodgkin lymphoma (B‐NHL), the prognostic impact of immune reconstitution (IR) remains ill‐defined, and detailed cross‐product comparisons have not been performed to date. In this retrospective observational study, we longitudinally characterized lymphocyte subsets and immunoglobulin levels in 105 B‐NHL patients to assess patterns of immune recovery arising after CD19 CAR‐T. Three key IR criteria were defined as CD4+ T helper (TH) cells > 200/µL, any detectable B cells, and serum immunoglobulin G (IgG) levels >4 g/L. After a median follow‐up of 24.6 months, 38% of patients displayed TH cells, 11% showed any B cells, and 41% had IgG recovery. Notable product‐specific differences emerged, including deeper TH cell aplasia with CD28z‐ versus longer B‐cell aplasia with 41BBz‐based products. Patients with any IR recovery experienced extended progression‐free survival (PFS) (median 20.8 vs. 1.7 months, p < 0.0001) and overall survival (OS) (34.9 vs. 4.0 months, p < 0.0001). While landmark analysis at 90 days confirmed improved PFS in patients with any recovery (34.9 vs. 8.6 months, p = 0.005), no significant OS difference was noted. Notably, 72% of patients with refractory disease never displayed recovery of any IR criteria. Early progressors showed diminished IR at the time of progression/relapse compared to patients with late progression/recurrence (after Day 90). Our results highlight the profound immune deficits observed after CD19 CAR‐T and shed light on the intersection of IR and efficacy in B‐NHL. Importantly, IR was impaired considerably postprogression, carrying significant implications for subsequent T‐cell‐engaging therapies and treatment sequencing.